Strengthening Literacy Competencies through Islamic Religious Education Learning in Elementary Schools - Shavira Salsabila; Mokh. Iman Firmansyah; Mohammad Rindu Fajar Islamy (Jurnal Elementaria Edukasia, 2024)
This study addresses the critical issue of low religious literacy among elementary students in Indonesia. It aims to explore how Islamic Education (PAI) teachers work to strengthen students' literacy competence through targeted learning systems. Employing Romiszowski's framework, the study analyzes problem identification, solution selection, implementation, and evaluation, using a phenomenological qualitative approach. Data were gathered through interviews, observations, and documentation. The findings show that religious literacy is primarily perceived as the ability to read and write, especially the Qur'an. Programs such as Literacy Week and Spiritual Friday significantly improved students' basic religious literacy. Students demonstrated notable progress in Qur'anic reading, advancing from pre-basic to basic proficiency, with some achieving a skilled level. These initiatives proved effective in raising students’ understanding and practice of religious literacy. This research contributes to a deeper understanding of the challenges surrounding religious literacy in Indonesian primary schools. It emphasizes the urgency of enhancing literacy competencies, particularly in religious contexts, for the future of education. By focusing on early education, this study underscores the need for sustained and innovative efforts to improve religious literacy, ensuring students are well-prepared for future educational challenges. Ultimately, it highlights the importance of creating a literate, well-rounded generation, capable of navigating a changing educational landscape.